PAPAN SEMEN-GYPSUM DARI CORE-KENAF (Hibiscus cannabinus L.) MENGGUNAKAN TEKNOLOGI PENGERASAN AUTOCLAVE (PERENNIAL, 2006)
Cement and gypsum bonded cellulosic fiber reinforced materials are ultimately ideal ecological building products. Their capability to use industrial coproducts and wastes as both their matrix material make its reinforcement also environmentally sustainable products. The objective of this study was to evaluate the effect of proportion cement-gypsum and curing autoclave time on the properties of cement gypsum board from core-kenaf. Three levels of proportion cement and gypsum were applied, namely; 40:60, 50:50, and 60:40, where cements contain at face-back layers and gypsum contain at core layers. Five levels of curing autoclave time were applied, namely ; conventional curing 2 weeks (control), curing autoclave 2, 4, 8, and 16 hours. CaCl2 3% and Borax 2 % was used as an accelerator and retarder. The physical and mechanical properties of cement-gypsum board were observed in according to JIS A 5417-1992. The results show that the physical and mechanical properties were gain on proportion of cement-gypsum 60:40 with 8 hours curing autoclave. Key words : Core-kenaf, Cement-gypsum board, Autoclave References